2021
DOI: 10.1161/circep.121.010042
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors Directly Block hERG-Potassium Channel and Independently Increase the Risk of QTc Prolongation in a Large Cohort of US Veterans

Abstract: Background - Worldwide, there are millions of chronic proton pump inhibitors (PPIs) users, often without a compelling indication. Evidence indicates that PPI treatment can increase mortality, in part due to a higher risk of QTc-related malignant arrhythmias. Drug-induced hypomagnesemia is currently believed to be the underlying mechanism, and therefore serum magnesium monitoring is recommended to minimize arrhythmic risk. However, recent data suggest that PPIs might also directly interfere with car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Our results indicated that pantoprazole increased the highest risk of QT prolongation among three PPIs, which may be attributed to the varying inhibition capacity of the Ikr among the three PPIs. Pantoprazole induced a higher inhibitory effect (82.8%) on the Ikr at a concentration of 100 µmol/L than lansoprazole (51.2%) and omeprazole (32.3%) [10]. Pantoprazole is the most frequent PPI related to TdP.…”
Section: Discussionmentioning
confidence: 86%
“…Our results indicated that pantoprazole increased the highest risk of QT prolongation among three PPIs, which may be attributed to the varying inhibition capacity of the Ikr among the three PPIs. Pantoprazole induced a higher inhibitory effect (82.8%) on the Ikr at a concentration of 100 µmol/L than lansoprazole (51.2%) and omeprazole (32.3%) [10]. Pantoprazole is the most frequent PPI related to TdP.…”
Section: Discussionmentioning
confidence: 86%
“…However, he had two medications that could have contributed to prolonged QTc. Haloperidol can cause QTc prolongation [ 9 ], and recent studies have reported that proton pump inhibitors (PPIs) such as omeprazole may also cause QTc prolongation through inhibition of the hERG-K channel [ 10 ]. The unidentified pills, empty haloperidol bottles, and prescribed omeprazole may presumptively be associated with the patient’s prolonged QTc.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of lansoprazole with other PPIs instead of no PPI addresses this confounding by indication, at least in part, because patients receiving lansoprazole and other PPIs were more likely to share similar comorbidities and concomitant medications. Proton pump inhibitors as a class may also prolong the QTc interval . Therefore, the comparison group of other PPIs was also useful to confirm that the drug interaction was specific to lansoprazole and excluded a PPI class effect by itself or with ceftriaxone.…”
Section: Discussionmentioning
confidence: 99%